BCT633: Construction economics and Islamic finance / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2020)
The general aim of this course is to introduce the principles of construction economics, construction supply and demand, the interpretation and the understanding of the process of cost planning, cost data, cost index and cost analysis utilizing the current information of a project. Besides, focuses on building design and cost implication towards building cost and the different building elements. It is also to understand and recognize the concept of life cycle costing and the calculation method of LCC to construct a new building. It is also will introduce basic concept of Islamic finance.